Mapping ecosystem services for policy support and decision making in the European Union - Maes, Joachim; Egoh, Benis; Willemen, Louise; Liquete, Camino; Vihervaara, Petteri; Schägner, Jan Philipp; Grizzetti, Bruna; Drakou, Evangelia G.; Notte, Alessandra La; Zulian, Grazia; Bouraoui, Faycal; Luisa Paracchini, Maria; et al. (Ecosystem services, 2012)
Mainstreaming ecosystem services into policy and decision making is dependent on the availability of spatially explicit information on the state and trends of ecosystems and their services. In particular, the EU Biodiversity Strategy to 2020 addresses the need to account for ecosystem services through biophysical mapping and valuation. This paper reviews current mapping methods, identifies current knowledge gaps and provides the elements for a methodological framework for mapping and assessing ecosystems and their services at European scale. Current mapping methodologies go beyond purely land cover based assessments and include the use of primary data of ecosystem services, the use of functional traits to map ecosystem services and the development of models and ecological production functions. Additional research is needed to cover marine ecosystems and to include the resilience of ecosystems to environmental change in spatially explicit assessments. The ecosystem services cascade which connects ecosystems to human wellbeing is argued to provide a suitable, stepwise framework for mapping ecosystem services in order to support EU policies in a more effective way. We demonstrate the use of this framework for mapping using the water purification service as case. ► Mainstreaming of ecosystem services into EU policy is dependent spatial information. ► We summarize current methods of mapping ecosystem services. ► We identify knowledge gaps in mapping ecosystem services. ► We propose a stepwise framework for mapping ecosystem services. ► We demonstrate the use of the framework for mapping using water purification.